The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4034/pboci.2011.114.19
|View full text |Cite
|
Sign up to set email alerts
|

Condições de Saúde Bucal, Acesso aos Serviços Odontológicos e Autopercepção de Saúde Bucal em Escolares de 12 anos

Abstract: Objetivo: Avaliar a condição de saúde bucal em escolares de 12 anos, na cidade de João Pessoa-PB, e identificar informações sobre acesso aos serviços odontológicos e autopercepção em saúde bucal. Método: Do universo composto por todos os indivíduos de 12 anos matriculados em estabelecimentos de ensino, a casuística foi constituída por 286 crianças que foram avaliadas por examinadores previamente calibrados. As crianças responderam a uma entrevista estruturada com variáveis referentes ao acesso aos serviços odo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…As for regional differences, we highlight the percentage of absence of gum disease, ranging from 41.6% in the Northern Region to 67.9% in the Southeastern Region (Brasil 2012). Comparing the results of this study with similar studies, we found that the condition of periodontal disease observed in this study was higher than those found in schoolchildren in the cities Itatiba, Goiânia and João Pessoa, 28.6%, 23.7% and 56.3% of the schoolchildren presented unhealthy gingival condition, respectively (Cangussu et al 2001;Freire et al 2010;Claudino et al 2011). However one of the possible factors may have contributed to the result this study in Manaus was only 20% sample belongs to Socioeconomic Classes A, Socioeconomic Classes B or Socioeconomic Classes C.…”
Section: Resultssupporting
confidence: 27%
“…As for regional differences, we highlight the percentage of absence of gum disease, ranging from 41.6% in the Northern Region to 67.9% in the Southeastern Region (Brasil 2012). Comparing the results of this study with similar studies, we found that the condition of periodontal disease observed in this study was higher than those found in schoolchildren in the cities Itatiba, Goiânia and João Pessoa, 28.6%, 23.7% and 56.3% of the schoolchildren presented unhealthy gingival condition, respectively (Cangussu et al 2001;Freire et al 2010;Claudino et al 2011). However one of the possible factors may have contributed to the result this study in Manaus was only 20% sample belongs to Socioeconomic Classes A, Socioeconomic Classes B or Socioeconomic Classes C.…”
Section: Resultssupporting
confidence: 27%